2014
DOI: 10.1515/chem-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of 14C and 36Cl in nuclear waste from Ignalina Nuclear Power Plant decommissioning

Abstract: On a first attempt, the determination of 14 C and 36 Cl activity concentrations in basic operational waste (spent ion-exchange resins and perlite mixture), in decommissioning waste (construction concrete, sand, stainless steel and serpentinite) and irradiated graphite from the Ignalina NPP has been performed. The samples for measurement of the specific activity of 14 C and 36 Cl were obtained from the selected places, where the highest values of the dose rate and the activity concentrations of gamma emitters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Axial distributions of the modeled 14 C, 3 H, 36 Cl, and 60 Co specific activities for the graphite columns with fuel channels in the RBMK-1500 reactor first peripheral part are presented in Figure 4. The measured specific activities of 14 C, 3 H, 36 Cl, and 60 Co from (Mazeika et al 2015) are also indicated as rhombs in Figure 4. Analogous axial distributions of the modeled specific activities of analyzed radionuclides were obtained for the remaining 10 groups of graphite columns as well, although these are not graphically presented here.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Axial distributions of the modeled 14 C, 3 H, 36 Cl, and 60 Co specific activities for the graphite columns with fuel channels in the RBMK-1500 reactor first peripheral part are presented in Figure 4. The measured specific activities of 14 C, 3 H, 36 Cl, and 60 Co from (Mazeika et al 2015) are also indicated as rhombs in Figure 4. Analogous axial distributions of the modeled specific activities of analyzed radionuclides were obtained for the remaining 10 groups of graphite columns as well, although these are not graphically presented here.…”
Section: Resultsmentioning
confidence: 96%
“…Sampling of the Ignalina NPP Unit 1 RBMK-1500 reactor graphite stack had been already done by the Ignalina NPP staff and it was expected that radiological characterization of the samples taken will be made during the course of the CAST project. However, over this time period no results of GR-280 grade graphite radiological characterization were made publicly available, except in a paper by Mazeika et al (2015). This paper presented preliminary studies of the experimental 14 C, 3 H, 36 Cl, and 60 Co activity measurements in several graphite sub-samples, attributed to the same sample of the GR-280 grade graphite bushing from the temperature channel of the Ignalina NPP Unit 1 RBMK-1500 reactor.…”
Section: Resultsmentioning
confidence: 99%
“…During the CAST project, a new numerical model for neutron activation was developed, and activity distribution of the 14 C within the whole reactor graphite stack at the Ignalina NPP was obtained. The measured 14 C content in the Ignalina NPP reactor GR-280 grade graphite reported in (Mazeika et al 2015) is 1.67 × 10 5 Bq g −1 . Combining this data with the new model, estimation of the 14 C inventory in the graphite stack was made (Narkunas and Poskas 2017).…”
Section: Source Termmentioning
confidence: 98%
“…There are several papers dealing with the problems of the irradiated Ignalina NPP graphite [Ancius et al, 2005, Mazeika et al, 2015, Narkunas et al, 2010, Plukiene et al, 2014, Remeikis et al, 2010, Smaizys et al, 2005 or the graphite of other NPPs with RBMK reactors [Bylkin et al, 2001, Bylkin et al, 2004. Some of them provide numerical estimations [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Smaizys et al, 2005], while others present experimental estimations [e.g. Mazeika et al, 2015] or combination of both [e.g. Remeikis et al, 2010].…”
Section: Introductionmentioning
confidence: 99%